Implementasi Metode Felics Pada Kompresi Citra Format GIF - Theresia Lumbantobing (CV. Graha Mitra Edukasi, 2025)
At this time, the increasingly rapid development of science and technology makes two-dimensional image files very necessary, where the resulting image size is large, requiring very large storage media, and other problems arise when exchanging data and information which increasingly consumes time and bandwidth. Therefore, a solution to the problem above emerged, namely by data compression. Data compression or data compression is a way in computer science to require smaller storage space, so that storage is more efficient. This is a compression method designed for grayscale images. The FELICS method presents a simpler system for lossless image compression that runs very quickly and only loses minimal compression efficiency. Implementation is the application or implementation, as an action to carry out the plan that has been made.